A Practical Quality Control Method for Saponins Without UV Absorption by UPLC-QDA - Zhao, Manjia; Dai, Yuntao; Li, Qi; Li, Pengyue; Qin, Xue-Mei; Chen, Shilin (Frontiers in Pharmacology, 2018)
Saponins are a class of important active ingredients. Analysis of saponin-containing herbal medicines is a major challenge for the quality control of medicinal herbs in companies. Taking the medicine Astragali radix (AR) as an example, it has been shown that the existing evaporative light scattering detection (ELSD) methods of astragaloside IV (AG IV) has the disadvantages of time-consuming sample preparation and low sensitivity. The universality of ELSD results in an inapplicable fingerprint with huge signals from primary compounds and smaller signals from saponins. The purpose of this study was to provide a practical and comprehensive method for the quality control of the astragalosides in AR. A simple sample preparation method with sonication extraction and ammonia hydrolyzation was established, which shortens the preparation time from around two days to less than 2 h. A UPLC-QDA method with the SIM mode was established for the quantification of AG IV in AR. Methanol extract was subjected to UPLC-QDA for fingerprinting analysis, and the common peaks were identified simultaneously with the QDA. The results showed that with the newly established method, the preparation time for a set of samples was less than 90 min. The fingerprints can simultaneously detect both saponins and flavonoids in AR. This simple, rapid, and comprehensive UPLC-QDA method is suitable for quality assessment of RA and its products in companies, and also provides references for the quality control of other saponin ingredients without UV absorption.